Characterising the impact of invasive species on microbial biofilms - Ng, Yuan Pei (Nanyang Technological University, 2020)
Currently, little is known about the stability of microbial biofilm communities in response to disturbances such as invasion. In this study, we standardised a novel in-vitro biofilm invasion model in static conditions. We subsequently examined the resistance and resilience of single- and dual-species resident biofilms of Pseudomonas aeruginosa and Pseudomonas protegens to pulse and press invasion by a pathogenic and a non-pathogenic strain of Klebsiella pneumoniae. Our results indicate that the peak disturbance occurred later than 2 h and 24 h after the end of pulse and start of press invasion respectively. Hence, quantifying resilience requires observations beyond the expected timepoints. The increase in resident community complexity from single- to dual-species did not increase the resistance to pulse invasion by the non-pathogenic K. pneumoniae strain but it led to an increase in functional resistance to press invasion, possibly due to nutrient limited conditions of press invasion. However, the increase in community complexity did not increase resident biofilm resistance to pulse and press invasion by the pathogenic strain of K. pneumoniae. The pathogenic strain of K. pneumoniae was also relatively more invasive and indicated possible synergism with P. aeruginosa. These results suggest that more invasive invaders can overcome the diversity-invasion effect.